Penguatan Kapasitas Masyarakat dalam Membuat Produk Olahan Jeruk Menuju Desa Agroindustri - Sudarmiatin Sudarmiatin; Rayie Tariaranie Wiguna; Adelia Shabrina Prameka (Jurnal Pengabdian UntukMu NegeRI, 2022)
Abstract Dau District is one of the sub-districts in Malang Regency, East Java which is famous for its citrus picking agro-tourism. However, not all villages in the Dau sub-district have orange gardens because only certain villages have citrus gardens. The abundance of oranges in Dau sub-district so far has only been sold directly in the form of citrus fruits and orange picking tours. So that the selling value of citrus fruits is still not maximized. Although Sumbersekar village is one of the villages in Dau sub-district, this village does not have citrus picking agro-tourism. For this reason, the people of Sumbersekar village can take advantage of the opportunity to become industrial entrepreneurs making processed citrus products. The purpose of the activity is to provide training to make citrus processed foods in order to create new entrepreneurs in Sumbersekar village. The target of the activity is PKK members who have a great desire to become new entrepreneurs in citrus production. The results of the activities showed a significant increase between before participating in the training and after participating in the training. Keywords: community capacity, processed citrus products